we’re all in this together - Rykov, María Helena (Contemporary Kanata: Interdisciplinary Approaches To Canadian Studies, 2021)
Poem Statement Job loss. Fear. Long line-ups. Supply chain disruptions. Empty store shelves. Transmission uncertainties. To mask or not to mask? Social isolation. Anxiety. Zoom-class teaching and learning. Parodying Cat Stevens, the first pandemic wave cut deepest. Constructed from found text in newspapers and City of Toronto press releases, this poem combines literary devices in ironic juxtaposition. The centred text content pulls out meanings and incongruities in relation to the text below. Even the text shading and font size communicates disparity: the centred darker, larger text imposes upon and partially obliterates the lighter, smaller text on which it rests. The COVID-19 pandemic highlights all-too-familiar inequities and disparities in the social fabric. We all suffer during this global health crisis, but some among us needlessly suffer more than others. We are not all in this together. Rather, we sail the same sea in different boats.